Postirradiation Osteosarcoma of the Maxilla: A Case Report and Current Review of Literature. (24th May 2009) - Chabchoub, Imene; Gharbi, Olfa; Remadi, Sami; Limem, Sami; Trabelsi, Amel; Hochlef, Makrem; Ben Fatma, Leila; Landolsi, Amel; Mokni, Moncef; Kraiem, Chekib; Ben Ahmed, Slim
Abstract : Background . Radiation-induced sarcomas are well-known potential late sequelae of radiation therapy. They are of rare occurrence in jaw bones and are even rarer in the maxilla. Case report . We report a case of radiation-induced osteosarcoma involving the maxilla in a patient treated with radiotherapy for nasopharyngeal carcinoma 14 years ago. Despite neoadjuvant chemotherapy, surgical treatment could not be performed, and the patient received palliative chemotherapy. Conclusions . Radiation-induced osteosarcomas are aggressive and often elude early detection and timely intervention, rapidly leading to early demise of afflicted patients. Long-term patient follow-up and a high index of suspicion are crucial for timely intervention.